STUDI TENTANG PENGARUH SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI DI PUSKESMAS CAKRANEGARA - Syafrudin; Muhamma Habibullah Aminy; Lale Ajeng Khalifatun Wardani; Slamet Mardiyanto Rahayu; Fathurrahman; Muhammad Aditya Rachman (Nusadaya Journal of Multidiciplinary Studies, 2024)
Based on the results of statistical analysis conducted in this study, there is a significant influence between Human Resources (HR) on Employee Performance at the Cakranegara Community Health Center. This is proven by: The significance value of the t-test is 0.000, which is smaller than the critical limit of 0.05, so that H₀ is rejected and H₁ is accepted; The regression coefficient value is 0.589, indicating that improving the quality of HR will improve employee performance; and the R Square value is 0.395, which means that 39.5% of the variation in employee performance can be explained by HR factors, while the rest is explained by other factors.